2021
DOI: 10.1186/s13000-021-01146-8
|View full text |Cite
|
Sign up to set email alerts
|

Periostin expression and its supposed roles in benign and malignant thyroid nodules: an immunohistochemical study of 105 cases

Abstract: Background Thyroid tumors are often difficult to histopathologically diagnose, particularly follicular adenoma (FA) and follicular carcinoma (FC). Papillary carcinoma (PAC) has several histological subtypes. Periostin (PON), which is a non-collagenous extracellular matrix molecule, has been implicated in tumor invasiveness. We herein aimed to elucidate the expression status and localization of PON in thyroid tumors. Method We collected 105 cases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…A previous study by the authors (9) and the present study demonstrated the overexpression of periostin in human TC cell lines, as well as in human TC tissues. Periostin overexpression in TC has been demonstrated to be related to poor prognostic features, including an advanced tumor stage, extrathyroidal extension, or lymph node metastasis (26)(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by the authors (9) and the present study demonstrated the overexpression of periostin in human TC cell lines, as well as in human TC tissues. Periostin overexpression in TC has been demonstrated to be related to poor prognostic features, including an advanced tumor stage, extrathyroidal extension, or lymph node metastasis (26)(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported in FTCs by Kusafuka et al . who demonstrated strong POSTN expression in the sclerotic stroma of the invasive region in widely invasive FTCs [ 29 ]. Our results corroborate the data shown in these studies, raising the possibility that POSTN may play a crucial role in capsular/vascular invasion processes in FTCs.…”
Section: Discussionmentioning
confidence: 99%
“…We found that in the classic PTC, the upregulated CD276 is also related to a poor prognosis. Periostin (POSTN) encoded a secreted extracellular matrix protein and is found to exhibit stromal deposition in invasive portions and cytoplasmic expression of undifferentiated thyroid carcinoma cells (52). Periostin has different expressions in different kinds of PTCs, and upregulated periostin could also be found in PTC compared to non-neoplastic tissues.…”
Section: Discussionmentioning
confidence: 99%